1997
DOI: 10.1073/pnas.94.17.9279
|View full text |Cite
|
Sign up to set email alerts
|

A T cell receptor antagonist peptide induces T cells that mediate bystander suppression and prevent autoimmune encephalomyelitis induced with multiple myelin antigens

Abstract: Experimental autoimmune encephalomyelitis (EAE) induced with myelin proteolipid protein (PLP) residues 139-151 (HSLGKWLGHPDKF) can be prevented by treatment with a T cell receptor (TCR) antagonist peptide (L144͞R147) generated by substituting at the two principal TCR contact residues in the encephalitogenic peptide. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
113
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 39 publications
0
113
1
Order By: Relevance
“…Furthermore, APLs are often immunogenic in their own right, expanding populations of APL-reactive T cells with the potential to cross-react with the native antigen (Nicholson et al, 1995;Das et al, 1997;Nicholson et al, 1997;Anderton et al, 1998;Anderton et al, 1999;Ausubel et al, 1999). This effect cannot be detected using monoclonal autoantigenspecific T cells.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, APLs are often immunogenic in their own right, expanding populations of APL-reactive T cells with the potential to cross-react with the native antigen (Nicholson et al, 1995;Das et al, 1997;Nicholson et al, 1997;Anderton et al, 1998;Anderton et al, 1999;Ausubel et al, 1999). This effect cannot be detected using monoclonal autoantigenspecific T cells.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This effect cannot be detected using monoclonal autoantigenspecific T cells. APL-reactive T cells will produce cytokines which may mediate bystander suppression of autoimmune responses (Nicholson et al, 1995;Greer et al, 1997;Nicholson et al, 1997;Cloake et al, 2014) or which may exacerbate inflammatory responses (Anderton et al, 1998;Anderton et al, 1999). Often, therefore, the immunogenic properties of an APL, rather than its direct effect on autoreactive T cells, have proven more valuable in the treatment of disease.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Variant peptides have therefore been exploited to manipulate autoreactive T cell responses in various autoimmune models including EAE. Several studies have demonstrated that altered peptide ligands (APL), which contain amino acid substitutions at TCR contact residues, are capable of preventing and ameliorating EAE [18][19][20][21]. Recently, we reported that a variant peptide containing an amino acid substitution at an MHC anchor residue anergized polyclonal MOG 35-55-specific T cells in vitro and reduced their encephalitogenicity in vivo upon adoptive transfer [22].…”
Section: Introductionmentioning
confidence: 99%
“…MP4 is processed into multiple determinants and can eliminate rodent EAE by promoting tolerance to different epitopes (19,20). This is important in view of epitope or determinant "spreading" in MS and EAE (19,20,(22)(23)(24)(25)(26)(27)(28). We previously documented epitope spreading in EAE in marmosets (29).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…We previously documented epitope spreading in EAE in marmosets (29). Epitope spreading poses a challenge for Ag-specific therapies, but even single epitopes can be effective in treating disease in some circumstances (27,28). For example, severe EAE induced in (PL/J ϫ SJL)F 1 mice by immunization with MOG [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and MBP Ac 1-11 peptides can be treated effectively by the MBP peptide alone (28).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%